2018
DOI: 10.1155/2018/1817542
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Bath Chemistry and Plating Variables on Characteristics of Electroless Ni–P Films on Si Wafers from Alkaline Citrate Solutions

Abstract: Electroless nickel–phosphorus (Ni–P) films were produced on the surface of p-type monocrystalline silicon in the alkaline citrate solutions. The influences of bath chemistry and plating variables on the chemical composition, deposition rate, morphology, and thermal stability of electroless Ni–P films on silicon wafers were studied. The as-deposited Ni–P films were almost all medium- and high-P deposits. The concentrations of Ni2+ and citric ions influenced the deposition rate of the films but did not affect P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…The reason why we observe an increase in C and O in Table is probably because of the accumulation of oxide and hydroxide upon potentiodynamic polarization, confirmed by the rise in the oxide peak intensity and shift toward larger binding energy in XPS (Figure d), and entrapment of citrate particles, enabling Ni–citrate complexes . Before the XPS measurements, gradual ion etching was applied to eliminate all of the surface adsorbents.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The reason why we observe an increase in C and O in Table is probably because of the accumulation of oxide and hydroxide upon potentiodynamic polarization, confirmed by the rise in the oxide peak intensity and shift toward larger binding energy in XPS (Figure d), and entrapment of citrate particles, enabling Ni–citrate complexes . Before the XPS measurements, gradual ion etching was applied to eliminate all of the surface adsorbents.…”
Section: Resultsmentioning
confidence: 81%
“…The reason why we observe an increase in C and O in Table 3 is probably because of the accumulation of oxide and hydroxide upon potentiodynamic polarization, confirmed by the rise in the oxide peak intensity and shift toward larger binding energy in XPS (Figure 6d), and entrapment of citrate particles, enabling Ni−citrate complexes. 64 Before the XPS measurements, gradual ion etching was applied to eliminate all of the surface adsorbents. After hydrogen production, since the etching mainly etched away this newly formed oxide and hydroxide layer, the entrapped citrate and remaining oxide layer increased their relative atomic percent values within the samples.…”
Section: Electrocoatingmentioning
confidence: 99%
“…Although nickel possesses electrocatalytic properties, and due to these properties is often used in industry, the overvoltage of hydrogen evolution (HER) on the nickel electrode is quite high, causing an increase in the energy consumption during its use. Therefore, in order to reduce overvoltage, nickel is often doped with other elements such as Mo [11], Co [12], P [13], Cu [14], etc. Besides, the results of water electrolysis on titanium and molybdenum electrodes from neutral (NaCl) and alkaline (NaOH) electrolytes showed that addition of Mo(VI) ions into the electrolyte activated HER [15].…”
Section: Introductionmentioning
confidence: 99%